Treatment outcomes of sialendoscopy for submandibular gland sialolithiasis: The minor axis of the sialolith is a regulative factor for the removal of sialoliths in the hilum of the submandibular gland using sialendoscopy alone. Issue 4 (August 2018) - Kondo, Norio; Yoshihara, Toshio; Yamamura, Yukie; Kusama, Kaoru; Sakitani, Eri; Seo, Yukako; Tachikawa, Mayako; Kujirai, Keiko; Ono, Erika; Maeda, Yasuyo; Nojima, Tomohito; Tamiya, Akiko; et al.
Abstract: Objective: To assess the general guidelines for the removal of sialoliths for submandibular gland sialolithiasis using sialendoscopy alone. Methods: We analyzed 61 sialoliths treated using sialendoscopy in 42 patients with submandibular gland sialolithiasis. We evaluated the submandibular gland sialoliths and divided each case based upon the location: the Wharton's duct or the hilum. We measured the major and minor axes of the sialoliths using a soft tissue computed-tomography (CT) scan and evaluated the removal rate of the sialoliths using sialendoscopy alone. Results: The removal rate of the sialoliths in the Wharton's duct (52.6%) was significantly higher than that in the hilum of the submandibular gland (26.1%) ( P = 0.042). The minor axis was significantly correlated to the treatment outcome of sialendoscopy alone for all cases ( P = 0.030). A significant correlation was observed for cases involving the hilum of the submandibular gland and the measurement of the minor axes of the sialoliths for the treatment outcome of sialendoscopy alone ( P = 0.009). The major axis showed no correlation with the treatment outcomes of sialendoscopy alone. Conclusion: The measurement of the minor axes of the sialoliths with a soft tissue CT scan was correlated with treatment outcome of sialendoscopy alone for all cases, particularly sialoliths in the hilum. The easurement of the major axis showed no correlation with outcomes of sialendoscopy alone.